Advertising Composition Selection Strategy to Strengthen the Language Message in Skincare Advertising on Tiktok - Asya Zahra; Reni Amali; Aisya Fatihah T.A; Muh Ary Fauzi; Muh Takwin (MultiTech Publisher, 2023)
This research aims to explain the composition of advertisements presented in advertising promotions on TikTok. The data source in this research is a TikTok video containing skincare advertisements for several products, namely skintific and lacoco dark spot. There are 3 points of advertising composition that must be considered, namely the main point consisting of an attractive ad title, stunning visuals, tagline, the body of the ad consisting of a product description and before and after and the closing of the ad consisting of a Call to Action (CTA), Logo and Information Contacts, testimonials and price mentions. However, it can be seen that the most dominant message content in skincare is stunning visuals, product descriptions and testimonials, because this is the key that can attract the audience to use it. So overall, the strategy for selecting ad composition on TikTok must consider visual strength, product delivery and testimonials. With a careful approach, skincare advertising can successfully strengthen language messages and achieve the desired marketing objectives.